1976
DOI: 10.1302/0301-620x.58b3.956242
|View full text |Cite
|
Sign up to set email alerts
|

The results of early treatment of typical congenital dislocation of the hip in Malmo

Abstract: The late results of early treatment of congenital dislocation of the hip in the von Rosen splint have been recorded in a follow-up study of 111 children with an average age of ten years (range eight to sixteen). The clinical diagnosis had been made within two days of birth and in most cases confirmed by radiological examination. Splintage was in all cases begun within the first few days and maintained for an average period of ten weeks. Two cases of failure of the initial treatment were encountered but had goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
37
2
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 6 publications
4
37
2
1
Order By: Relevance
“…Cyvin (1977) found residual radiographic changes in children after treatment with the Freika pillow; some needed additional treatment with casts or operations. This is in contrast to Fredensborg's ( 1976) observation that CDH children developed completely normal hips: only in two cases were there suspected radiographic changes in the course of the treatment, but these were without harmful consequences for the further development of the hips.…”
contrasting
confidence: 95%
“…Cyvin (1977) found residual radiographic changes in children after treatment with the Freika pillow; some needed additional treatment with casts or operations. This is in contrast to Fredensborg's ( 1976) observation that CDH children developed completely normal hips: only in two cases were there suspected radiographic changes in the course of the treatment, but these were without harmful consequences for the further development of the hips.…”
contrasting
confidence: 95%
“…No cases of femoral head necrosis were seen. It has been shown that this is an extremely rare complication when the von Rosen splint is used, 3 probably because this splint permits a certain degree of movement in the flexed and abducted hips. Six children who have reached walking age have been lost to follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown the von Rosen splint to be effective, [14][15][16] but the use of the Pavlik harness has become more widespread in recent years. There is no previous published comparison of the von Rosen splint and the Pavlik harness.…”
Section: Discussionmentioning
confidence: 99%